Determination of the Volume Expansion Coefficient of Liquids (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
This article analyzes the methods of determining the volume expansion coefficient of a liquid. The volume expansion coefficient represents the relative change in the volume of a liquid depending on the temperature change. Formulas for calculating the coefficient of volume expansion for various liquids are presented in the framework of the study, and the methods of their experimental determination are discussed. Volumetric expansion applies not only to liquids, but also to solids and gases. Factors affecting the accuracy of experimental results and ways to reduce them are also considered. The obtained information is of great importance in researching the physical properties of liquids and their application in various fields.